Modulation of brain oscillations during fundamental visuo-spatial processing: A comparison between female collegiate badminton players and sedentary controls. (March 2015) - Wang, Chun-Hao; Tsai, Chia-Liang; Tu, Kuo-Cheng; Muggleton, Neil G.; Juan, Chi-Hung; Liang, Wei-Kuang
Abstract: Objectives: The present study aimed to investigate the difference in fundamental cognitive processing and neural oscillations between badminton players and sedentary controls. Design: A cross-sectional design was adopted to address this issue. Methods: We compared time-frequency electroencephalographic (EEG) activity from collegiate female badminton players ( n  = 12, aged 20.58 ± 2.75 years) and age-and gender-matched sedentary non-athletic controls ( n  = 13, aged 19.08 ± 2.10 years) when they performed a task that involves visuo-spatial attention and working memory. Results: We observed that players responded faster than controls on the task without suffering any increase in error responses. Correspondingly, the players, relative to controls, exhibited higher task-related modulations in beta power in the attention condition as well as in theta and beta power in the working memory condition. Notably, the behavior-EEG correlations revealed that better attention performance is associated with lower beta power, while greater working memory is related to higher theta power. Conclusions: Our results shed light on the mechanisms of athletic superiority in fundamental cognitive functioning: the higher theta synchronization points to a greater engagement of attention, whereas the higher beta desynchronization supports the contribution of processing speed (or motor-related processing) to better performance in athletes. This study extends current understanding by suggesting that enhanced neurocognitive function seen in athletes may transfer to fundamental tasks, giving insight into the generalizability of sport experience to neurocognitive functioning. Highlights: The difference in neural oscillations between athletes and controls was tested. Athletes outperformed controls on visuo-spatial cognitive function. Athletes showed relatively higher theta and lower beta power. Neurocognitive correlation may help explain this athlete-control difference. Sport-related benefits can be assessed using tasks without sport-specific content.